Breathing is coupled with voluntary action and the cortical readiness potential - Hyeong-Dong Park (Nature Portfolio, 2020)
Voluntary action and free will have been associated with cortical activity, referred to as “the readiness potential” that precedes self-initiated actions by about 1 s. Here, the authors show that the involuntary and cyclic motor act of breathing is coupled with voluntary action and the readiness potential.